CALCULATION OF EXCITON LUMINESCENCE IN SOLID SOLUTIONS - Abduvakhit Abdukadirov (Western European Studies, 2024)
The problem of developing theoretical methods for studying the energy distribution of localized photo-carriers in refractory materials in order to calculate photoconductivity and photoluminescence spectra is actual. А2B6 semiconductor compounds and their solid solutions, due to their optical, photoluminescent and photosensitive properties, are promising materials for science and technology, are widely used in optoelectronic technology as fluorescent screens, scintillation sensors, photodetectors, laser structural elements. These straight-band semiconductors, having high radiation efficiency, cover the entire spectrum range from the ultraviolet to the IR region [1]. In the constructed model, the function p(ɛ) determining the luminescence spectrum of a solid solution and the energy density of the generation rate G(ɛ) for different exciton lifetimes are calculated. For a more detailed comparison of theoretical calculations with experimental data [4,7], the density function of states was replaced by a threeparameter function that significantly affects the change in the half-width and the position of the maximum of the exciton luminescence spectrum, which is confirmed by the results of numerical calculations
Keywords: lifetime; tunnel jump; spectrum